Depolimerisasi Kitosan Menggunakan Sinar Ultraviolet dan Katalis Asam Klorida: Depolymerization of chitosan with ultraviolet ray and chloride acid catalyst - Devi Faustine; Iriani Setyaningsih; Safrina Dyah Hardiningtyas (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2020)
Chitosan is a natural product of chitin deacetylation which has a long molecular chain and high molecular weight, this makes chitosan constrained in the process of its application. To overcome this, it is necessary to do a depolymerization process that can reduce the molecular weight of chitosan and shorten the molecular chain of chitosan. Chitosan depolymerization in this study was carried out using ultraviolet radiation and strong acids to use chitosan polymer chains to produce chitosan with shorter chains and can be used in water or neutral solvents. Depolymerization begins with dissolving chitosan with hydrochloric acid solution, then irradiated with ultraviolet light for 45 minutes, 60 minutes, 75 minutes. Chitosan solution was precipitated using isopropyl alcohol, and filtered with 40 mesh nylon cloth. Chitosan which has a pH of seven is dried to get chitosan dissolved air. The air soluble chitosan obtained was analyzed by comparing each given administration and chitosan control. The use of ultraviolet light and HCl solutions designed to depolymerize the characteristics of chitosan produced. Selected based on chitosan depolymerized with 75 minutes of ultraviolet light irradiation with yield of 70.07±14.00%, solubility 99.80±0.17%, white degree 99.99±0.00%, viscosity 49.78±0.31 cP, molecular weight 169.46±0.30 kDa, and zeta potential 73.03±1.92 mV. The decrease in molecular weight and viscosity on the characteristics of water-soluble chitosan shows that the process of chitosan depolymerization occurs when the depolymerization effect increases with the duration of ultraviolet light irradiation.